2020
DOI: 10.1186/s12970-019-0332-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine supplementation on physical performance and mood dimensions in elite and trained-recreational athletes

Abstract: Background Caffeine supplementation (CAFF) has an established ergogenic effect on physical performance and the psychological response to exercise. However, few studies have compared the response to CAFF intake among athletes of different competition level. This study compares the acute effects of CAFF on anaerobic performance, mood and perceived effort in elite and moderately-trained recreational athletes. Methods Participants for this randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 83 publications
5
40
1
2
Order By: Relevance
“…In line with previous research [ 41 , 42 ], a 6 to 20 RPE scale of Borg (1978) [ 33 ] was presented as soon as participants finished the Wingate test. Accordingly, participants were first asked to report RPE regarding perceived exertion at legs (RPE muscular ); second, participants were asked to report RPE only at cardiorespiratory level (RPE cardio ); and finally, participants had to declare global RPE (RPE general ), which included features from both muscular and cardiorespiratory levels.…”
Section: Methodsmentioning
confidence: 93%
“…In line with previous research [ 41 , 42 ], a 6 to 20 RPE scale of Borg (1978) [ 33 ] was presented as soon as participants finished the Wingate test. Accordingly, participants were first asked to report RPE regarding perceived exertion at legs (RPE muscular ); second, participants were asked to report RPE only at cardiorespiratory level (RPE cardio ); and finally, participants had to declare global RPE (RPE general ), which included features from both muscular and cardiorespiratory levels.…”
Section: Methodsmentioning
confidence: 93%
“…In response to the high demands for isometric strength and resistance that sailors must face [11,12], as well as the high % VO 2max they reach as the speed increases [9,14], those athletes who consume caffeine (20% sailors of international level and 25% of those of national level) can benefit from the use of this supplement. Since the molecular form resembles that of adenosine, caffeine blocks adenosine receptors, activating the central nervous system, which decreases the subjective perception of effort, while enhancing glycolytic metabolism, neuromuscular recruitment, and the bioavailability of calcium in myoplasm [52]; moreover, previous studies have demonstrated its ergogenic effect on the improvement of muscle strength [53] and in the face of high-intensity efforts [54].…”
Section: Discussionmentioning
confidence: 99%
“…In rugby, caffeine supplementation has been shown to be effective to increase performance in a battery of rugby-specific tests [ 65 ]. Moreover, the ergogenic effect of caffeine on mood and physical performance is similar in normal and elite athletes [ 66 ] and may be a suitable supplementation for amateur and professional rugby players. Nevertheless, the prevalence of caffeine supplementation in this sample is lower than that of Olympic athletes, where its consumption has been detected in 76% of them [ 67 ].…”
Section: Discussionmentioning
confidence: 99%